Diversity and US Foreign Policy : a Reader. - Wilson III, Ernest J. (Routledge, 2004)
This book brings together the most recent and best work on multiculturalism and foreign policy, examining European, Latino, Asian, Jewish, African and Arab-Americans and their relationship to US foreign policy making.